2009
DOI: 10.1016/j.peptides.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 receptor activation inhibits c-Jun N-terminal kinase activity and promotes insulin signaling

Abstract: The melanocortin system is crucial to regulation of energy homeostasis. The melanocortin receptor type 4 (MC4R) modulates insulin signaling via effects on c-Jun N-terminal kinase (JNK). The melanocortin agonist NDP-MSH dose-dependently inhibited JNK activity in HEK293 cells stably expressing the human MC4R; effects were reversed by melanocortin receptor antagonist. NDP-MSH time-and dose-dependently inhibited IRS-1 ser307 phosphorylation, effects also reversed by a specific melanocortin receptor antagonist. NDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
3
27
0
3
Order By: Relevance
“…[31][32][33] In addition, melanocortin system has been recently shown to modulate insulin signaling via c-Jun N-terminal kinase activity. 34 Impairment of POMC protein synthesis was associated, in our patient, with a Cushingoid phenotype and severe metabolic alterations despite the normal hypothalamic-pituitary-adrenal function. This sits easily with the observation that POMC-null mice are hypersensitive to adverse effects of glucocorticoids in terms of development and accumulation of fat mass, hyperglycemia and insulin resistance.…”
Section: Discussionmentioning
confidence: 56%
“…[31][32][33] In addition, melanocortin system has been recently shown to modulate insulin signaling via c-Jun N-terminal kinase activity. 34 Impairment of POMC protein synthesis was associated, in our patient, with a Cushingoid phenotype and severe metabolic alterations despite the normal hypothalamic-pituitary-adrenal function. This sits easily with the observation that POMC-null mice are hypersensitive to adverse effects of glucocorticoids in terms of development and accumulation of fat mass, hyperglycemia and insulin resistance.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, the increased POMC gene expression may be related to the JNK inhibition. Chai et al (2009) found that the alteration of POMC receptor activation (melanocortin-4 receptor) could participate in the regulation of JNK activity in HEK293 cells. Although p38 MAPK and ERK signalling can regulate appetite in mammals (Morikawa et al, 2004;Kim et al, 2010), acute acetate treatment did not affect the level of phosphorylation of p38 MAPK and ERK proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For the JNK pathway, NDP-α-MSH does-dependently inhibits JNK in HEK293 cells stably expressing MC4R [78]. AMPK phosphorylation level was demonstrated to be decreased by MC4R activation with MTII in PVH neurons and NDP-α-MSH stimulation in MC4R-transfected HEK293T cells [56, 74].…”
Section: Intracellular Signaling Pathways Of Neural Mcrsmentioning
confidence: 99%